Dielectric behaviour of glasses and glass ceramics in the system BaO-PbO-TiO2-B2O3-SiO2 - Mandal R.K.; Prasad Ch.D.; Parkash O.M.; Kumar D. (My University, 2025)
Glasses with varying molar ratios of PbO/BaO in the system BaO-PbO-TiO2-B2O3-SiO2 were prepared keeping (BaO + PbO)/TiO2 ratio equal to one. The glasses were ceramized by two-stage heat treatment. X-ray diffraction indicates that PbTiO3 crystallizes in lead-rich glasses while BaTiO3 precipitates in barium-rich compositions. Solid solution (Ba, Pb)TiO3 does not seem to crystallize over the entire range of compositions. Simultaneous presence of PbO and BaO in the initial glass composition reduces the yield of ferroelectric phase. Dielectric properties have been interpreted in terms of microstructural features. © 1987 Indian Academy of Sciences.